1989
DOI: 10.1017/s002221510010934x
|View full text |Cite
|
Sign up to set email alerts
|

An avoidable occupational hazard during mastoid surgery

Abstract: Conjunctival innoculation is a previously unrecognized hazard for the otologist during mastoid surgery. This experiment assesses the spread of droplet contamination during temporal bone dissection. The results suggest that otologists and assistants should wear eye protection during exposure of the mastoid antrum by drilling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…This is in agreement with our prior analysis of droplet spread during mastoidectomy, in which cadaveric tissue was detected 6 ft from the surgical site 12 . In a separate study, the spread of particulates generated during mastoidectomy was noted at a maximum of 41 cm away 22 . Together with the current study, there is evidence of both droplet spread and aerosol generation during mastoidectomy, but no direct evidence for SARS‐CoV‐2 transmission.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with our prior analysis of droplet spread during mastoidectomy, in which cadaveric tissue was detected 6 ft from the surgical site 12 . In a separate study, the spread of particulates generated during mastoidectomy was noted at a maximum of 41 cm away 22 . Together with the current study, there is evidence of both droplet spread and aerosol generation during mastoidectomy, but no direct evidence for SARS‐CoV‐2 transmission.…”
Section: Discussionsupporting
confidence: 91%
“…There was significant heterogeneity among the three studies and only one study was deemed clinically relevant and of adequate quality [49]. The three studies were found describing aerosolization of bone dust and contaminated irrigation fluid (Table 9) [49][50][51]. Aggregated Evidence: Grade D: three experimental studies.…”
Section: Mastoid Surgerymentioning
confidence: 99%
“…Theatre nurses are likely to be at less risk than surgeons since they are generally further from the operative field. However, Lannigan et al (1989) have demonstrated that irrigation fluid during temporal bone dissection may spread up to 41 cm from the point of drilling and we have noticed splashes on the theatre nurse's spectacles following mastoid surgery. We will be investigating this further in order to determine how frequently such contamination occurs.…”
Section: Eye Protectionmentioning
confidence: 96%
“…The Department of Health (1990) recommended that the mucous membranes of the eyes, mouth and nose should be protected from blood splashes and the Joint Working Party of the Hospital Infection Society and the Surgical Infection Study Group (1992) advised that extra precautions including eye protection should be taken when operating on patients known to be hepatitis B or HIV positive and in 'high risk' cases including orthopaedic procedures involving power tools. Recent articles have supported these recommendations (Lannigan et al, 1989;Prior et al, 1993).…”
Section: Eye Protectionmentioning
confidence: 98%